2023
DOI: 10.1128/mbio.02296-22
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dual Base Editor Systems (iACBEs) for Simultaneous Conversion of Adenine and Cytosine in the Bacterium Escherichia coli

Abstract: Dual base editors are DSB-free CRISPR tools applied in eukaryotes but not yet in bacteria. We developed an improved ACBE toolset for bacteria, combining highly processive deaminases. We believe that the bacterial optimized iACBE toolset is a significant advancement in CRISPR-based E. coli genome editing and adaptable to other microbes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…We found only one protospacer containing 14 nucleotides as the spacer of the gRNA for the SNV at ISM-RS04210 edited with gRNA04 (Figure S3), showing that this off-target event resulted from the CRISPR-Cas system targeted editing. These data demonstrated that most of the mutations were the products of random deamination, while still, part of the mutations resulted from CRISPR-Cas-mediated targeting which is in accordance with previous reports on Agrobacterium spp., S. coelicolor , S. elongatus , and Escherichia coli. , Overall, our base editing system is a reliable method for genetic manipulation with limited off-target events, but whole-genome sequencing may be necessary to identify undesired mutations in the genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found only one protospacer containing 14 nucleotides as the spacer of the gRNA for the SNV at ISM-RS04210 edited with gRNA04 (Figure S3), showing that this off-target event resulted from the CRISPR-Cas system targeted editing. These data demonstrated that most of the mutations were the products of random deamination, while still, part of the mutations resulted from CRISPR-Cas-mediated targeting which is in accordance with previous reports on Agrobacterium spp., S. coelicolor , S. elongatus , and Escherichia coli. , Overall, our base editing system is a reliable method for genetic manipulation with limited off-target events, but whole-genome sequencing may be necessary to identify undesired mutations in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…These data demonstrated that most of the mutations were the products of random deamination, while still, part of the mutations resulted from CRISPR-Cas-mediated targeting which is in accordance with previous reports on Agrobacterium spp., 23 S. coelicolor, 24 S. elongatus, 26 and Escherichia coli. 22,28 Overall, our base editing system is a reliable method for genetic manipulation with limited off-target events, but whole-genome sequencing may be necessary to identify undesired mutations in the genome.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Base editors facilitate nucleotide substitutions within the editing window through the action of adenine or cytosine deaminases. Efforts to increase editing efficiency have continued through the utilization of deaminase variants and Cas9 variants obtained via laboratory evolution. Recently, dual base editors have been used to perform both adenine and cytosine conversions. Due to their lack of causing DSBs, base editors exhibit low cytotoxicity and offer the advantage of not requiring donor template DNA, thus making them widely used in various microbes …”
Section: Crispr-cas-mediated Genome Editing Methodsmentioning
confidence: 99%
“…Given the requirement for microbial dual-BE tools, researchers subsequently developed an ACBE (ABE8e-CDA-nCas9) system applied in Bacillus subtilis and an iACBE (evoCDA1-ABE9e-nCas) system in E. coli, respectively. , Notably, the efficiencies of ABE8e-CDA-nCas9 and iACBE were both up to 100%, which exhibited their great potential for microbial genome editing.…”
Section: Constructions Of Be-based Microbial Gene-editing Toolsmentioning
confidence: 99%